The use of Gene-Xpert MTB RIF in the diagnosis of extrapulmonary tuberculosis in childhood and adolescence - Rafaela Baroni Aurilio; Vivian Vidal Marsili; Thiago da Silva Santos Malaquias; Afrânio Lineu Kritski; Clemax Couto Sant’Anna (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Gene-Xpert MTB RIF (Xpert) is based on nucleic acid amplification by real-time polymerase chain reaction, which allows for the identification of Mycobacterium tuberculosis and rifampin resistance. We describe the use of Xpert for extrapulmonary tuberculosis (EPTB) in children and adolescents. METHODS: A case series of two reference centers in Rio de Janeiro from 2014-2019. RESULTS: The final diagnosis of EPTB was established in 11/36 (31%) patients, with five cases detectable by Xpert. For lymph node evaluation (9/11), diagnosis by Xpert occurred in 5/9 patients, all with caseous aspects. CONCLUSIONS: Xpert can facilitate the rapid diagnosis of lymph node tuberculosis.